Beradaptasi Untuk Berkembang: Studi Kualitatif Pengalaman Wirausahawan Penyandang Disabilitas Dalam Mengatasi Tantangan - Wibowo, Martino; Yanto Sidik Pratiknyo; Budi Santosa; Sid Suntrayuth (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to investigate the challenges and opportunities faced by entrepreneurs with disabilities in Indonesia in running their businesses. The study used a qualitative approach with a case study method to explore real-life contexts. Data were obtained through semi-structured interviews with 10 small and medium-sized entrepreneurs with disabilities and 15 non-disabled respondents. The results show that entrepreneurs with disabilities face significant barriers, including limited access to capital, infrastructure issues, and societal stigma. Despite this, they demonstrate resilience and adaptability. Internal factors include motivation, family support, and skills development, while external factors include market understanding, competitive awareness, and supplier relationships. Furthermore, strategic competencies such as continuous self-improvement, collaboration, and the ability to influence the social and regulatory environment have been shown to play a crucial role in their success. The study's conclusions emphasize the need for targeted support through inclusive entrepreneurship programs, increased access to technology, and the creation of a disability-friendly business environment to strengthen the sustainability of entrepreneurs with disabilities. Keywords: Adaptation, Business, Disability, Entrepreneur, Entrepreneurship, Inclusivity.